Randomized, placebo‐controlled, double‐blind phase I trial of co‐administered pyronaridine and piperaquine in healthy adults of sub‐Saharan origin - Andrea Kuemmerle; Denis Gossen; Annick Janin; Andrew Stokes; Nada Abla; Maja Szramowska; Ulrike Lorch; Myriam El Gaaloul; Isabelle Borghini‐Fuhrer; Stephan Chalon (Wiley, 2024)
Abstract Drug resistance to sulfadoxine‐pyrimethamine and amodiaquine threatens the efficacy of malaria chemoprevention interventions in children and pregnant women. Combining pyronaridine (PYR) and piperaquine (PQP), both components of approved antimalarial therapies, has the potential to protect vulnerable populations from severe malaria. This randomized, double‐blind, placebo‐controlled (double‐dummy), parallel‐group, single site phase I study in healthy adult males or females of Black sub‐Saharan African ancestry investigated the safety, tolerability, and pharmacokinetics of PYR + PQP (n = 15), PYR + placebo (n = 8), PQP + placebo (n = 8), and double placebo (n = 6) administered orally once daily for 3 days at the registered dose for the treatment of uncomplicated malaria. All participants completed the study. Forty‐five adverse events were reported in 26 participants, most (41/45) were mild/moderate in severity, with no serious adverse events, deaths, or study withdrawals. Adverse events were reported in 66.7% (10/15) of participants administered PYR + PQP, 87.5% (7/8) with PYR + placebo, 50.0% (4/8) with PQP + placebo, and 83.3% (5/6) with placebo. For PYR containing regimens, five of 23 participants had asymptomatic transient increases in alanine and/or aspartate aminotransferase. With PQP containing regimens, four of 23 participants had mild Fridericia‐corrected QT interval prolongation. Liver enzyme elevations and prolonged QTc interval were consistent with observations for PYR‐artesunate and dihydroartemisinin‐PQP, respectively, administered to healthy adults and malaria patients. Increases in PYR and PQP exposures were observed following co‐administration versus placebo, with substantial interparticipant variability. The findings suggest that PYR + PQP may have potential in chemoprevention strategies. Further studies are needed in the target populations to assess chemoprotective efficacy and define the benefit-risk profile, with special considerations regarding hepatic and cardiac safety.